Kecemasan Statistika pada Mahasiswa Program Sarjana Pendidikan Agama Islam Universitas Islam Negeri Walisongo Semarang - Dwi Yunitasari; Muhammad Iqbal (Justek : Jurnal Sains dan Teknologi, 2020)
Abstract: The high level of student’s statistics anxiety  affects the performance of students in the study of statistics. The measurement of statistical anxiety is still rarely done, and the measurement results are also vary.  This study explores the level of student's statistical anxiety in the Islamics Education undergraduate program at UIN Walisongo Semarang who took the statistics course in the odd semester of 2020/2021. Research respondents were 70 people. To measure the level of anxiety of statistics students, an instrument of measurement that is used is the Statistical Anxiety Rating Scale (STARS) at the three factors first, namely: Test and class anxiety, Interpretation Anxiety, and Fear of Asking for Help. Observations carried out by way of filling the questionnaire by the students, and analysis of data using analysis of statistics descriptive. Results of the study showed the levels of statistics anxiety for undergraduate student at the Islamic Study of UIN Walisongo Semarang is an amount to 31%. The factors that most trigger statistical anxiety are tests and class activity. If differentiated by the type of sex, then a student of women experiencing anxiety statistics are more substantial than the students of men.Abstrak: Tingginya level kecemasan statistika (statistics anxiety) mahasiswa mempengaruhi performa mahasiswa dalam belajar statistika. Pengukuran kecemasan statistika masih jarang dilakukan, dan hasil pengukurannya juga beragam. Penelitian ini mengeksplorasi level kecemasan statistika mahasiswa pada program sarjana PAI UIN Walisongo Semarang yang mengambil matakuliah statistika pada semester gasal 2020/2021. Responden penelitiannya adalah 70 orang. Untuk mengukur level kecemasan statistika mahasiswa, instrumen pengukuran yang digunakan adalah  Statistical Anxiety Rating Scale (STARS) dengan dengan tiga faktor pertama, yaitu:, Test and class anxiety, Interpretation Anxiety, dan Fear of Asking for Help. Observasi dilakukan dengan cara pengisian kuesioner oleh mahasiswa, dan analisis data menggunakan analisis statistika deskriptif. Hasil penelitian menunjukkan level kecemasan statistika mahasiswa program sarjana PAI UIN Walisongo Semarang adalah sebesar 31%. Faktor yang paling memicu kecemasan statistika adalah ujian dan kegiatan perkuliahan (Test and Class Anxiety). Jika dibedakan berdasarkan jenis kelamin, maka mahasiswa perempuan mengalami kecemasan statistika yang lebih besar dibandingkan mahasiswa laki-laki.